Research on the Tourist Attraction of Amusement Theme Parks Based on Tourist Experience - Chen, Haiming; Guan, Wenxi (International Journal of Global Economics and Management, 2024)
This paper takes the Shunde Overseas Chinese Town Happy Coast Park as an example, using literature research and online text analysis methods to process and analyze 1459 online comments. The research results show that the attractiveness of Shunde Overseas Chinese Town Happy Coast Park lies in its unique cultural atmosphere and amusement facilities, while its disadvantages are the overcrowding during holidays, prolonged playtime, and high package ticket prices. These findings provide a reference for other amusement-type theme parks in strengthening their unique cultural atmosphere and package ticket sales model.